2010
DOI: 10.1152/ajpendo.00701.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hyperinsulinemic euglycemic step clamping with tracer glucose infusion and labeled glucose infusate for assessment of acute insulin resistance in pigs

Abstract: Gjessing PF, Fuskevåg O, Hagve M, Revhaug A, Irtun Ø. Hyperinsulinemic euglycemic step clamping with tracer glucose infusion and labeled glucose infusate for assessment of acute insulin resistance in pigs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…This correlates with the findings of Gjessing et al. [28] who showed that basal‐ and insulin‐stimulated glucose utilization was twice as high in pigs compared to human beings. The group also demonstrated moderate peripheral and hepatic insulin unresponsiveness as a result of surgical trauma [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This correlates with the findings of Gjessing et al. [28] who showed that basal‐ and insulin‐stimulated glucose utilization was twice as high in pigs compared to human beings. The group also demonstrated moderate peripheral and hepatic insulin unresponsiveness as a result of surgical trauma [28].…”
Section: Discussionsupporting
confidence: 91%
“…[28] who showed that basal‐ and insulin‐stimulated glucose utilization was twice as high in pigs compared to human beings. The group also demonstrated moderate peripheral and hepatic insulin unresponsiveness as a result of surgical trauma [28]. In this respect, the use of a percutaneous model in our study with avoidance of trauma is important.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental protocol with 5 consecutive HECs by progressively increasing insulin infusion rates allows differentiation between impaired peripheral insulin sensitivity and response. 17,18 Because dexamethasone treatment affected ISI significantly only during HEC-I and HEC-II, we propose that the observed peripheral insulin resistance is predominately characterized by decreased insulin sensitivity and less by decreased insulin response (assessed as SSGIR and ISI during the highest insulin infusion rate during HEC-IV and HEC-V).…”
Section: Discussionmentioning
confidence: 97%
“…Basal glucose turnover was assessed during the last 30 min of a 90-min-long primed (6 mg/kg) continuous (0.12 mg·kg Ϫ1 ·min Ϫ1 ) infusion of D- [6,6-2 H2]glucose (basal period), followed by peripheral and hepatic insulin sensitivity measurements consisting of two consecutive 120-min-long hyperinsulinemic (ϳ15 and 40 IU/ml) euglycemic (ϳ4.5 mmol/l) clamps with labeled glucose infusate (2.1 atom %enrichment). Insulin was infused at rates of 0.4 (low-insulin clamp) and 1.2 mU·kg Ϫ1 ·min Ϫ1 (high-insulin clamp) to differentiate between hepatic and peripheral insulin sensitivity, as described previously (20).…”
Section: Animalsmentioning
confidence: 99%
“…Determination of tracer enrichment in arterial blood measured by LC-MS/MS and calculations of endogenous glucose release and whole body glucose disposal were performed based on modified versions of Steele's equations (18,51), as described previously (20).…”
Section: Animalsmentioning
confidence: 99%